Oxidative Stress and Inflammation Caused by Cisplatin Ototoxicity - Vickram Ramkumar; Debashree Mukherjea; Asmita Dhukhwa; Leonard P. Rybak (Antioxidants, 2021)
Hearing loss is a significant health problem that can result from a variety of exogenous insults that generate oxidative stress and inflammation. This can produce cellular damage and impairment of hearing. Radiation damage, ageing, damage produced by cochlear implantation, acoustic trauma and ototoxic drug exposure can all generate reactive oxygen species in the inner ear with loss of sensory cells and hearing loss. Cisplatin ototoxicity is one of the major causes of hearing loss in children and adults. This review will address cisplatin ototoxicity. It includes discussion of the mechanisms associated with cisplatin-induced hearing loss including uptake pathways for cisplatin entry, oxidative stress due to overpowering antioxidant defense mechanisms, and the recently described toxic pathways that are activated by cisplatin, including necroptosis and ferroptosis. The cochlea contains G-protein coupled receptors that can be activated to provide protection. These include adenosine A1 receptors, cannabinoid 2 receptors (CB2) and the Sphingosine 1-Phosphate Receptor 2 (S1PR2). A variety of heat shock proteins (HSPs) can be up-regulated in the cochlea. The use of exosomes offers a novel method of delivery of HSPs to provide protection. A reversible MET channel blocker that can be administered orally may block cisplatin uptake into the cochlear cells. Several protective agents in preclinical studies have been shown to not interfere with cisplatin efficacy. Statins have shown efficacy in reducing cisplatin ototoxicity without compromising patient response to treatment. Additional clinical trials could provide exciting findings in the prevention of cisplatin ototoxicity.